New species of Oregmopyga (Coccoidea, Eriococcidae) of Peru, description of immature stages - Granara de Willink, Maria Cristina (2007)
The adult female, the first nymfal stage (indetermined sex), the second stage of the female and male of Oregmopyga peruviana sp. nov. found on Vitis vinifera in Perú are described; a key for the species is included. The genus is new for South America.